Learning about Pesticide Use Adapted from Ethnoscience as a Contribution to Green and Sustainable Chemistry Education - Robby Zidny; Ingo Eilks (MDPI AG, 2022)
This study shows how students can learn about green and sustainable chemistry by using the knowledge perspective of a local indigenous culture as a starting point. This learning approach encourages students to learn chemistry by connecting culture with learning about green chemistry. The cultural context selects the use of a phytochemical agent (d-limonene) from a local plant (Citrus grandis), which is a traditional botanical pesticide that is used by the Baduy tribe in Western Java, Indonesia. A simple low-cost extraction method that uses a kitchen microwave was chosen to introduce modern green extraction methods to learners. This facilitates the students' ability to evaluate the "greenness" of this method, as compared to more conventional extraction methods, such as Soxhlet and steam distillation. The learning activities were conducted during the COVID-19 pandemic with the help of an online learning management system (SPADA) and Google Meet. The students' feedback and selected results are discussed below.